You Killed Me First - Marrs, John, (Freelance journalist) (Seattle : Thomas & Mercer, 2025)
"It's 5 November, and a woman awakens to a nightmare. Bound and gagged, she lies trapped in the heart of a towering bonfire. As the smoke thickens, panic sets in -- she's moments away from being engulfed in flames. How did it come to this? Rewind eleven months: Margot, a faded TV star, and her long-suffering friend Anna watch as glamorous Liv and her flawless family move into their street. The three women soon fabricate the perfect pretence of friendship, but each harbours her own deadly secret - and newcomer Liv senses something is terribly wrong beneath the polished exteriors. As cracks widen in the veneer of perfection and lies escalate out of control, tension ignites. Bonfire Night is approaching and someone is set to burn...But who will it be?" --
Keywords: Female friendship -- Fiction; Neighbors -- Fiction; Psychological fiction; Thrillers (Fiction)